Dielectric properties of ferromagnetic Ni nanoparticles added (Cu0.5Tl0.5)Ba2Ca2Cu3O10−δ superconducting phase - Mumtaz, M.; Asghar, Mian A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2018)
Ferromagnetic nickel (Ni) nanoparticles were added in (Cu0.5Tl0.5)Ba2Ca2Cu3O10−δ (CuTl-1223) superconducting matrix to get Nix/CuTl-1223; x = 0–1.00 wt% nanoparticles-superconductor composites. Temperature- and frequency-dependent dielectric properties of CuTl-1223 superconducting phase with different contents of Ni nanoparticles were studied. Different dielectric parameters such as dielectric constant (ε′r,ε′′r), dielectric tangent loss (tan δ) and ac conductivity (σac) were determined from experimentally measured capacitance and conductance at different frequencies from 10 kHz to 10 MHz and at different operating temperatures from 78 to 290 K. The values of ε′r and ε′′r were found maximal at smaller frequencies and started to decrease at higher frequencies. The value of σac is high at high frequency unlike to ε′r and ε′′r, which is due to release of space charges at high frequencies. Peaks in tan δ graphs represent the resonance phenomenon at certain frequencies in these samples. Non-monotonic behavior in variation of dielectric parameters with temperature of Nix/CuTl-1223 samples was observed particularly at high temperatures which was due to thermal instability of the system at high temperatures.